Resposta da modulação autonômica cardiovascular à mudança postural, contração e treinamento da musculatura do assoalho pélvico em gestantes - Corrêa, Mikaela da Silva (Universidade Federal de São Carlos, 2018)
Pelvic floor muscle training is encouraged during pregnancy for the prevention of pelvic floor muscle dysfunctions. It is known that the contraction and training of others small muscle groups can cause changes in the autonomic nervous system (ANS) modulation, but this was not verified regarding the pelvic floor muscles (PFM). In pregnancy, cardiovascular autonomic responses to different stimuli may present differences in relation to non-pregnant individuals, due to adaptations of this period. Different analyzes and standardized stimuli provide complementary information on the functioning of ANS, which is not yet fully elucidated during pregnancy. This study consists of two manuscripts with the following aim: Study 1: To evaluate the response of the cardiovascular autonomic modulation to the postural change through different analyzes in the second trimester of pregnancy. Study 2: to evaluate if there is alteration in the cardiovascular autonomic modulation after the contraction of the PFM in pregnant, and if there is effect of the PFM training in the cardiovascular autonomic modulation at rest during pregnancy. Study 1 was a cross-sectional study where we evaluated the response of heart rate (HRV) and blood pressure variabilities (BPV) and baroreflex sensitivity (BRS) to postural change in pregnancy at the 18th week, and not pregnant women of the same range age. In study 2, we evaluated the HRV, BPV and BRS response after a series of PFM contractions in 18-week pregnant. The pregnant were divided into 2 groups, in which one performed PFM training from the 20th to the 35th week of pregnancy, and one control group without training. In the 36th week, HRV, BPV and BRS were compared at rest of the two groups. Conclusions: In study 1 we verified that HRV, parasympathetic modulation and BRS are reduced in pregnant at rest, while the complexity of HRV and BPV is maintained. The responses to postural change occur in the same direction with some differences, such as lower proportion in relation to vagal withdrawal and sympathetic activation. In study 2, we verified that there was no change in HRV, BPV and SBR after a series of PFM contractions, and that pregnant presented lower blood pressure (BP) and sympathetic modulation of BP, and higher BRS at 36 weeks of pregnancy compared to untrained pregnant women.
Keywords: Gravidez; Sistema nervoso autônomo; Sistema cardiovascular; Barorreflexo; Treinamento; Pregnancy; Autonomic nervous system; Cardiovascular system; Baroreflex; Training; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL